Developing Arabic Teaching Methods Using Google Sites for Middle School Students - A’isyatuzzuhrah, A’isyatuzzuhrah; Nasution, Sahkholid (Lughawiyah: Journal of Arabic Education and Linguistics, 2024)
Teaching Arabic in schools proceeds traditionally, where education is still from one source and through limited and different means, as is the case in the Pena Santri Middle School in Medan, where students have become less active and motivated in learning Arabic. Therefore, we were in dire need of developing an appropriate method, such as Google Sites. The aim of the research is to describe the method of developing methods for teaching the Arabic language to students at Pena Santre Middle School in Medan, and to know its specifications and effectiveness to improve students’ motivation in learning the Arabic language. This research is developmental research, as the researchers used the 4-D method, which consists of 4 stages, which are definition, design, development, and publication. All these stages later result in a product that will be tested to ensure its suitability before testing it with students.  In the introduction stage, eighth grade students at Pena Santre School need a teaching method that can increase their interest in learning the Arabic language. In the design stage, the two researchers design a product that is considered compatible with the students’ needs, which is Google Sites, which consists of three parts. After completing the design, the two researchers validated it with very valid results. The result of the research is that the educational tool Google developed websites increases students’ motivation in learning Arabic, especially for the patient clinic subject.